Ischemic Benefit and Hemorrhage Risk of Ticagrelor-Aspirin Versus Aspirin in Patients With Acute Ischemic Stroke or Transient Ischemic Attack. Issue 11 (November 2021) - Johnston, S. Claiborne; Amarenco, Pierre; Aunes, Maria; Denison, Hans; Evans, Scott R.; Himmelmann, Anders; Jahreskog, Marianne; James, Stefan; Knutsson, Mikael; Ladenvall, Per; Molina, Carlos A.; Nylander, Sven; et al.
Abstract : Background and Purpose: In patients with acute mild-moderate ischemic stroke or high-risk transient ischemic attack, the THALES trial (Acute Stroke or Transient Ischemic Attack Treated With Ticagrelor and Aspirin for Prevention of Stroke and Death) demonstrated that when added to aspirin, ticagrelor reduced stroke or death but increased risk of severe hemorrhage compared with placebo. The primary efficacy outcome of THALES included hemorrhagic stroke and death, events also counted in the primary safety outcome. We sought to disentangle risk and benefit, assess their relative impact, and attempt to identify subgroups with disproportionate risk or benefit. Methods: In a randomized, placebo-controlled, double-blind trial of patients with mild-to-moderate acute noncardioembolic ischemic stroke or high-risk transient ischemic attack, patients were randomized within 24 hours after symptom onset to a 30-day regimen of either ticagrelor plus aspirin or matching placebo plus aspirin. For the present analyses, we defined the efficacy outcome, major ischemic events, as the composite of ischemic stroke or nonhemorrhagic death, and defined the safety outcome, major hemorrhage, as intracranial hemorrhage or hemorrhagic death. Net clinical impact was defined as the combination of these 2 end points. Results: In 11 016 patients (5523 ticagrelor-aspirin and 5493 aspirin), a major ischemic event occurred in 294 patients (5.3%) in the ticagrelor-aspirin group and in 359 patients (6.5%) in the aspirin group (absolute risk reduction 1.19% [95% CI, 0.31%–2.07%]). Major hemorrhage occurred in 22 patients (0.4%) in the ticagrelor-aspirin group and 6 patients (0.1%) in the aspirin group (absolute risk increase 0.29% [95% CI, 0.10%–0.48%]). Net clinical impact favored ticagrelor-aspirin (absolute risk reduction 0.97% [95% CI, 0.08%–1.87%]). Findings were similar when different thresholds for disability were applied and over a range of predefined subgroups. Conclusions: In patients with mild-moderate ischemic stroke or high-risk transient ischemic attack, ischemic benefits of 30-day treatment with ticagrelor-aspirin outweigh risks of hemorrhage. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03354429. Abstract : Supplemental Digital Content is available in the text.